1986
DOI: 10.1002/cber.19861191112
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselektive Katalyse, 4. Synthese N‐substituierter (R,R)‐3,4‐Bis(diphenylphosphino)‐pyrrolidine und Anwendung ihrer Rhodiumkomplexe zur asymmetrischen Hydrierung von α‐(Acylamino)acrylsäure‐Derivaten

Abstract: Eine einfache Synthese von (R.R)-3,4-Bis(diphenylphosphino)pyrrolidin (6a)und Rhodium Complexes for the Asymmetric Hydrogenation of a-(Acy1arnino)acrylic Acid DerivativesA simple synthesis of (R,R)-3,4-bis(diphenylphosphino)pyrrolidine (6a) and some N-substituted derivatives 6b-m is described. 61 and 6m are optically active tetraphosphanes, composed of two (R,R)-3,4-bis(diphenylphosphino)pyrrolidine units and a dicarboxylic residue. The structure of the parent compound 6a was determined by X-ray diffraction. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(53 citation statements)
references
References 18 publications
(1 reference statement)
1
51
1
Order By: Relevance
“…The reaction of (3R,4R)3,4-bis(diphenylphosphino)-pyrrolidine (Pyrphos, R,R-1) [12] with commercially available 1-pyrenebutyric acid in the presence of 1,3-dicyclohexylcarbodiimine (DCC) and 4-(dimethyl-A C H T U N G T R E N N U N G amino)pyridine (DMAP) afforded ligand (R,R)-2 in high yield (94%). [13] When evaluating the performance of ligand (R,R)-2 in the Rh(I)-catalyzed asymmetric hydrogenation of a-dehydroamino esters 3, we found that the introduction of a pyrenyl group into the Pyrphos ligand did not affect its enantioselectivity (Table 1).…”
Section: Communicationsmentioning
confidence: 99%
“…The reaction of (3R,4R)3,4-bis(diphenylphosphino)-pyrrolidine (Pyrphos, R,R-1) [12] with commercially available 1-pyrenebutyric acid in the presence of 1,3-dicyclohexylcarbodiimine (DCC) and 4-(dimethyl-A C H T U N G T R E N N U N G amino)pyridine (DMAP) afforded ligand (R,R)-2 in high yield (94%). [13] When evaluating the performance of ligand (R,R)-2 in the Rh(I)-catalyzed asymmetric hydrogenation of a-dehydroamino esters 3, we found that the introduction of a pyrenyl group into the Pyrphos ligand did not affect its enantioselectivity (Table 1).…”
Section: Communicationsmentioning
confidence: 99%
“…Contrary to the previous experience in the synthesis of pyrrolidine diphosphines with non-aromatic amines [18], the synthesis of (R,R)-N-phenyl-3,4-bis(diphenylphosphino)pyrrolidine (2) using an aromatic amine posed quite a few problems, requiring the use of specific reduction conditions, use of the trifliloxy leaving group instead of the mesyloxy and use of the more reactive potassium diphenylphosphide instead of the in situ prepared sodium diphenylphosphide. The newly established synthetic sequence is outlined in Scheme 1.…”
Section: Ligand Synthesismentioning
confidence: 88%
“…However, looking at the structure of 2 determined by X-ray crystallography and comparing it with the structures of analogous pyrrolidine diphosphines [18,[24][25][26][27], of which 1 is an example, we observed significant explanatory differences.…”
Section: Enantioselective Catalysis Experimentsmentioning
confidence: 91%
See 1 more Smart Citation
“…The reactions were run at 50 bar hydrogen pressure for 24 h. After identification of the most promising catalysts by HPLC analysis of the reaction products the results were confirmed by upscaling and performance of the hydro- genation in individual trials. Among 48 ligands tested Prophos [18] and DeguPHOS [19] were superior and induced enantioselectivities of 40 ± 60% ee in the product. The most efficient reaction was achieved by application of a catalyst which was obtained from [Rh(COD) 2 ]OTf and (R)-NORPHOS.…”
Section: Mechanistic Investigationsmentioning
confidence: 99%